Reduction of Sodium Migration in Polymers by Addition of 15-Crown-5 Ether as Getter Substance. (1st January 2017) - Schwab, S.; Jung, J. P. H.; Appenroth, J.; Pittenauer, E.; Allmaier, G.; Gruber, S.; Bauer, M.; Miethaner, S.; Nelhiebel, M.; Hutter, H.
Abstract : Already small amounts of ion contamination within sensitive areas of high voltage transistors can cause severe damage to semiconductor devices. Therefore, it is of utmost importance to hinder mobile ions from reaching critical regions (e.g., the gate oxide layer). To protect semiconductor devices from environmental influences and contamination, polymers are used for chip encapsulation. Reduction of ion migration within these polymers can increase the reliability of the semiconductor device. Crown ethers are well known to form stable complexes with alkali cations. Within this work the influence of 15-crown-5 ether on the sodium migration in poly-methyl methacrylate and polyimide will be evaluated by means of ion conductivity measurements.